(untitled) (Conferencea, 2023)
It is a state order that the future specialists of the field - regardless of who they are, whether they are university students or students of secondary special educational institutions, have theoretical knowledge at the level of the educational materials of the state program of physical culture of preschool educational institutions related to the culture of the human body.